2021
DOI: 10.3390/ani11071971
|View full text |Cite
|
Sign up to set email alerts
|

Zoo Visitor Attitudes Are More Influenced by Animal Behaviour than Environmental Enrichment Appearance

Abstract: Decisions on environmental enrichment programmes are sometimes based on the assumption that non-natural or artificial looking items negatively affect visitor experiences. In this study, we developed a questionnaire to assess zoo visitor attitudes towards enrichment appearance in an outdoor walk-through enclosure for ring-tailed lemurs (Lemur catta). Naturalistic and artificial looking enrichment items were alternately provided in the enclosure. A total of 371 visitors filled out the questionnaire: 174 in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Impact of perceived aggression on welfare perceptions may vary amongst species, as for example Markwell [109] reported that zoo visitors expected to witness aggression in Tasmanian devils and were disappointed if aggressive behaviour was absent. More consistently, beliefs about play and affiliative social behaviours (like allogrooming), translated to perceptions of positive welfare [10, 16, 36, 47, 72, 73, 95, 96, 99, 110, 111]. Yet play behaviours can appear extreme and even violent [112], and communication signals mediating social interactions between animals are often quite subtle [113].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Impact of perceived aggression on welfare perceptions may vary amongst species, as for example Markwell [109] reported that zoo visitors expected to witness aggression in Tasmanian devils and were disappointed if aggressive behaviour was absent. More consistently, beliefs about play and affiliative social behaviours (like allogrooming), translated to perceptions of positive welfare [10, 16, 36, 47, 72, 73, 95, 96, 99, 110, 111]. Yet play behaviours can appear extreme and even violent [112], and communication signals mediating social interactions between animals are often quite subtle [113].…”
Section: Resultsmentioning
confidence: 99%
“…Use of environmental enrichment consistently had a positive impact on welfare perceptions [18, 29, 35, 37, 38, 43, 44, 47, 50, 54, 62, 64, 73, 90, 93, 94, 96, 97, 99102, 107, 110, 116, 119, 131, 133139], including feeding-related enrichment [99102, 136, 138]. Positive perceptions of feeding enrichment are not surprising, as the act of feeding in any circumstance increased welfare perceptions [61, 95, 99, 102]. Yet not all visitors were aware of enrichment in general [139] or which items within an enclosure are enriching [40, 99].…”
Section: Resultsmentioning
confidence: 99%
“…‐Note that recent study suggests visitors respond more to the behavior elicited by the enrichment than its appearance (Salas et al, 2021)…”
Section: Current Benefits and Challenges Of Cognitive Research In Zoosmentioning
confidence: 99%
“…Challenge Potential negative outcomes Options to limit/overcome challenge -Consider placing research in protected areas and using a video link or changes in height to allow visitors to spectate at a safe distance (Macdonald & Whiten, 2011). -Note that recent study suggests visitors respond more to the behavior elicited by the enrichment than its appearance (Salas et al, 2021) Reluctance Past negative experience with researchers or perception of research output.…”
Section: Human-basedmentioning
confidence: 99%
“…Research has shown that zoo visitors place animal welfare one of the zoo’s top priorities ( Roe et al, 2014 ). The behavior of the animals in the zoo is a key influence over visitor perception of their care and welfare ( Salas et al, 2021 ). Animals that are viewed as thriving in the zoo impart more influence over the visitor’s experiences of the zoo and therefore are better tools to use to enact planetary friendly human behavior change.…”
Section: Future Research To Further Understand Wellbeing As An Aim Of...mentioning
confidence: 99%